2013
DOI: 10.1155/2013/253483
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Modeling of Lectin-Like Protein fromAcacia farnesianaReveals a Possible Anti-Inflammatory Mechanism in Carrageenan-Induced Inflammation

Abstract: Acacia farnesiana lectin-like protein (AFAL) is a chitin-binding protein and has been classified as phytohaemagglutinin from Phaseolus vulgaris (PHA). Legume lectins are examples for structural studies, and this family of proteins shows a remarkable conservation in primary, secondary, and tertiary structures. Lectins have ability to reduce the effects of inflammation caused by phlogistic agents, such as carrageenan (CGN). This paper explains the anti-inflammatory activity of AFAL through structural comparison … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…Moreover, differences observed in the presence of proteolytic activity in albumins and globulin fractions reinforce the differences in protein content between fractions. These hypothesis suggest that the anti-inflammatory activity previously reported by AFAL (Abrantes et al, 2013) and pharmacolocgical activities observed here should be promoted by different lectins present in A. farnesiana seeds.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Moreover, differences observed in the presence of proteolytic activity in albumins and globulin fractions reinforce the differences in protein content between fractions. These hypothesis suggest that the anti-inflammatory activity previously reported by AFAL (Abrantes et al, 2013) and pharmacolocgical activities observed here should be promoted by different lectins present in A. farnesiana seeds.…”
Section: Discussionsupporting
confidence: 62%
“…These plant proteins receive special attention, as they are promising molecules for human therapeutic treatment. Recently, Abrantes et al (2013) purified a lectin-like protein with anti-inflammatory activity from albumin fraction A. farnesiana. In the present work, we evaluated the presence of anti-inflammatory and analgesic activities in the globulin fraction obtained from A. farnesiana seeds.…”
Section: Introductionmentioning
confidence: 99%
“…(Fabaceae) is known as sweet acacia, needle bush, and huisache. A. farnesiana, due to its proteins, lectin, and α-amyrin, β-amyrin, and lupeol have anti-inflamma tory and antioxidant effects and can down-regulate proinflammatory mediators [375][376][377].…”
Section: Other Plants With Lower Evidence For Lupus Conditionsmentioning
confidence: 99%
“…Areole 6.5-7 mm long, 4 mm wide [10]. A. farnesiana is one of the medicinally important plants of Ayurvedic system of medicine and has been used for various pharmacological activities such as Vibrio cholera inhibition [11], herbicide [12], antimalarial [13], antioxidant [14], antidiarrheal [15], antimicrobial [16], phytoremediation [17], defluoridation, adsorbent [18], antiulcer [19], acetylcholine esterase, NADH oxidase inhibitory [20], bronchodilator [21], and anti-inflammatory [22]. The compounds, viz., lectin-like protein, cyclopropenoid fatty acids [23], four new diterpenes, acasiane A, acasiane B, farnesirane A, and farnesirane B [24], methyl gallate [25], naringenin, kaempferol, quercetin, and myricetin [26] have been isolated from various parts of the plant.…”
Section: Introductionmentioning
confidence: 99%